(untitled) (Journal of the College of Basic Education, 2023)
A test is an important device for teachers and for learners; for teachers in that it helps to assess the students’ EL performance and for learners in that it helps them to discover the areas of weakness and strength in their performances. Dictation is one of the integrative tests that have proved their proficiency in measuring different language skills, like listening comprehension and spelling . It is a reading passage (100 to 200 words) which is read by the teacher three times at a normal speed . The students’ task is to write down what the teacher read in the second reading . However, experienced instructors in the field of TEFL realise that learners have many errors in writing . Hence, the present study aims at identifying, classification and explaining the errors that EFL college students make during applying dictation tests . The sample of the study is 55 students randomly chosen from the second- year students at the Department of English, College of Basic Education , Al-Mustansiriyah University during the academic year 2005 / 2006. The instrument of the study is a ready test which consists of a 162- word passage. The passage is intended to test advanced students’ dictation. The test is submitted to a jury of specialists to ensure its validity. The test results revealed that the sample subjects have many errors which the researcher classified into comprehension, grammatical and spelling errors. Spelling errors formed the largest percentage of the total number of errors which are, in turn, classified into subcategories . In the light of the obtained results some conclusions are drawn, number of recommendations are made, and several suggestions for further research are presented .